Clinical Relevance of Hepatic and Renal P‐gp/BCRP Inhibition of Drugs: An International Transporter Consortium Perspective. Issue 3 (22nd June 2022) - Taskar, Kunal S.; Yang, Xinning; Neuhoff, Sibylle; Patel, Mitesh; Yoshida, Kenta; Paine, Mary F.; Brouwer, Kim L.R.; Chu, Xiaoyan; Sugiyama, Yuichi; Cook, Jack; Polli, Joseph W.; Hanna, Imad; et al.
Abstract : The role of P‐glycoprotein (P‐gp) and breast cancer resistance protein (BCRP) in drug–drug interactions (DDIs) and limiting drug absorption as well as restricting the brain penetration of drugs with certain physicochemical properties is well known. P‐gp/BCRP inhibition by drugs in the gut has been reported to increase the systemic exposure to substrate drugs. A previous International Transporter Consortium (ITC) perspective discussed the feasibility of P‐gp/BCRP inhibition at the blood–brain barrier and its implications. This ITC perspective elaborates and discusses specifically the hepatic and renal P‐gp/BCRP (referred as systemic) inhibition of drugs and whether there is any consequence for substrate drug disposition. This perspective summarizes the clinical evidence‐based recommendations regarding systemic P‐gp and BCRP inhibition of drugs with a focus on biliary and active renal excretion pathways. Approaches to assess the clinical relevance of systemic P‐gp and BCRP inhibition in the liver and kidneys included (i) curation of DDIs involving intravenously administered substrates or inhibitors; (ii) in vitro ‐to‐ in vivo extrapolation of P‐gp‐mediated DDIs at the systemic level; and (iii) curation of drugs with information available about the contribution of biliary excretion and related DDIs. Based on the totality of evidence reported to date, this perspective supports limited clinical DDI risk upon P‐gp or BCRP inhibition in the liver or kidneys.